A Novel Two-Stage Alumina Reactor System for Burning Volatiles Generated in Situ from Biosolid: Effect of Pyrolysis Temperature and Combustion Conditions on PM1 Emission - Liaw, Sui Boon; Deng, C.; Wu, Hongwei (American Chemical Society, 2018)
© 2018 American Chemical Society. A novel two-stage alumina reactor system is developed for studying particulate matter (PM) emission from in situ volatiles combustion. It enables the generation of in situ volatiles at different pyrolysis temperatures (up to 1300 °C) and the subsequent combustion of in situ volatiles in air and oxyfuel at 1300 °C. It is found that the PM emitted from volatiles combustion contains only PM with aerodynamic diameter <1 µm (PM1) and has a unimodal distribution. An increase in pyrolysis temperature from 1100 to 1300 °C results in a substantial increase in PM1yield and a shift of fine mode diameter from 0.043 to 0.108 µm. The PM1emitted from the volatiles generated at 1100 °C mainly consists of Na, K, S, and P. For PM1emitted from the volatiles generated at 1300 °C, there are substantial increases in the yield of Na, K, and P; in addition, Mg and Si are present in PM1because of the release of these inorganic species from biosolid into the volatiles. For trace elements, increasing pyrolysis temperature from 1100 to 1300 °C not only increases the As and Cd yields in PM1but also results in the presence of Cr, Cu, and Mn in PM1because of increasing As and Cd volatility and the release of Cr, Cu, and Mn from biosolid into the volatiles. The yields of V and Pb remained unchanged, and there is no Ti, Ni, and Co present in the PM1. Changing the combustion atmosphere from air to oxyfuel causes a slight increase in PM1yield due to increased formation of alkali sulfates and enhanced formation of P4O10but results in no changes in the yields and particle size distributions of trace elements. Further analysis indicates the Na, K, S, and Cl are present in the PM1emitted from the combustion of volatiles produced at 1100 °C in the form of Na and K sulfates and Cl while P is present in the form of P4O10. The P in PM1is present in the forms of Na, K, and Mg metaphosphates and P4O10where higher proportion of P4O10is formed in PM0.1-1when pyrolysis temperature increases to 1300 °C. It is also evident that (Na, K)PO3and P4O10vapors can react with the alumina reactor tube to form alkali aluminophosphate glass which is then retained in the furnace, leading to only a fraction of Na and K in the volatiles being collected as PM1after combustion.